The Tradition of Seeing Hari Bulan in Starting A Life Cycle Ritual in The North Kluet Community, South Aceh, Indonesia - Abdul Manan; Ramadha Lianda; Aslam Nur (Fakultas Ushuluddin, Adab dan Humaniora (FUAH) UIN Kiai Haji Achmad Siddiq Jember, 2024)
Abstract: The implementation of the life cycle rituals of the Kluet community often begins with seeing Hari Bulan so that nothing undesirable happens. This research aims to find out the origin of Hari Bulan, the meaning of Hari Bulan, the determination of Hari Bulan, and the preservation of Hari Bulan. This is qualitative research conducted in North Kluet District, South Aceh. The data source was obtained from local traditional leaders who know well about Hari Bulan. Data collection techniques were carried out using interviews, observation, and documentation. Data analysis uses the Miles and Huberman interactive data analysis model. The findings show that the origin of Hari Bulan was not clearly revealed when it appeared in Northern Kluet society. Hari Bulan cannot be separated from the origin of the arrival of Islam itself in Aceh, especially in North Kluet. In one month there are good and bad Hari Bulan. Therefore, the Kluet people carry out life cycle rituals on auspicious days according to Hari Bulan. To preserve it, we need mobilizers, observers, and supporters from various levels of society to keep maintaining and developing a strong motivation to participate in the preservation of the tradition of seeing Hari Bulan.